1976
DOI: 10.1136/hrt.38.10.1053
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmias in syndrome of balloon deformity of mitral valve. Definition of possible high risk group.

Abstract: Twenty patients clinically identified as having balloon deformity of the mitral valve were studied to assess the incidence of ventricular arrhythmias. Echocardiography and phonocardiography were used to confirm the nature of the mitral valve lesion. Continuous 24-hour electrocardiograms were obtainedfrom all patients and analysed by a computer and 2 observers. One patient had ventricularfibrillation and 3 patients had ventricular tachycardia. There was a high incidence of other less severe forms of ventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(9 citation statements)
references
References 23 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Boudoulas et al [412] and Campbell et al [414] found that infero-lateral ST segment changes were associated with the presence of ventricular tachycardia or fibrillation. It was concluded from other studies that prolongation of QT interval and increased QT dispersion might be useful markers of arrhythmic mortality [415,416] .…”
Section: Sudden Cardiac Death 1411mentioning
confidence: 99%
“…Boudoulas et al [412] and Campbell et al [414] found that infero-lateral ST segment changes were associated with the presence of ventricular tachycardia or fibrillation. It was concluded from other studies that prolongation of QT interval and increased QT dispersion might be useful markers of arrhythmic mortality [415,416] .…”
Section: Sudden Cardiac Death 1411mentioning
confidence: 99%
“…SCA has been described as one of the possible outcomes on follow-up in MVP 4, 5 and several instances of SCA in young patients with MVP have been reported 6, 7 . Additionally, occurrence of ventricular arrhythmias on resting or ambulatory electrocardiograms is reported to be higher among patients with MVP 8, 9 though some studies have disputed this finding 10 . Conversely, other natural history studies indicate that MVP may have a benign prognosis 2, 4 .…”
Section: Introductionmentioning
confidence: 99%
“…5,9,10,[28][29][30][31][32][33][34][35] In particular, the clinical evidence of hemodynamically important regurgitation greatly affects the occurrence of ventricular arrhythmias. However, the detection of MVP in survivors of life-threatening arrhythmias suggests that a true association between hemodynamically uncomplicated MVP and arrhythmic SCD may exist.…”
Section: Ventricular Arrhythmias In Mvpmentioning
confidence: 99%